Biomechanical study of distal radioulnar joint ballottement test - Tadanobu Onishi (2018)
© 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. We investigated the reliability and accuracy of the distal radioulnar joint (DRUJ) ballottement test using five fresh-frozen cadaver specimens in triangular fibrocartilage complex (TFCC)-intact, and TFCC-sectioned wrists. The humerus and proximal ulna were fixed. The ulna was allowed to translate in dorsopalmar directions without rotation, and the radius was allowed to move freely. Four sensors of a magnetic tracking system were attached to the radius and ulna, and the nails of each examiner's thumbs. Five examiners conducted the DRUJ ballottement test before and after TFCC sectioning. We used two techniques: With holding and without holding the carpal bones to the radius (holding and non-holding tests, respectively). We compared the magnitudes of bone-to-bone (absolute DRUJ) movement with that of the examiner's nail-to-nail (relative DRUJ) movement. The intrarater intraclass correlation coefficients (ICCs) were 0.92 (holding) and 0.94 (non-holding). The interrater ICCs were 0.84 (holding) and 0.75 (non-holding). Magnitudes of absolute and relative movements averaged 11.5 and 11.8 mm, respectively (p < 0.05). Before TFCC sectioning, the DRUJ movement during the holding and non-holding techniques averaged 9.8 and 10.8 mm, respectively (p < 0.05). The increase in DRUJ movement after TFCC sectioning was greater with the holding technique (average 2.3 mm) than with the non-holding technique (average 1.6 mm). The DRUJ ballottement test with magnetic markers is relatively accurate and reliable for detecting unstable joints. We recommend the holding technique for assessing DRUJ instability in clinical practice. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1123–1127, 2017.